Microstructure and Mechanical Properties of (Ti, Nb)C Ceramic-Reinforced 316L Stainless Steel Coating by Laser Cladding - Jinsu Yu; Hsinshen Ho (Applied Sciences, 2022)
The poor wear resistance of 316L stainless steel restricts further practical application. In this study, to improve its microhardness and wear resistance, the TiC and NbC ceramic particles were introduced to 316L powder fabricate (Ti, Nb)C ceramics-reinforced composite coatings by laser cladding. The effects of ceramics addition on the phase composition, microstructure, microhardness, and wear properties of the composite coating were investigated with an X-ray diffractometer, optical microscopy, scanning electron microscopy, a Vickers hardness tester, and a multi-functional surface performance tester. Results indicate that the TiC and NbC ceramic particles were distributed at the grain boundaries, effectively inhibiting the grain growth and refining the microstructure. The addition of ceramic particles could have decreased the temperature gradient and promoted the transformation from columnar crystals to equiaxed crystals. In addition, the microhardness was improved due to fine grain strengthening and solid solution strengthening. The friction coefficient and cross-sectional area of the composite coating were 0.381 and 8164.732 μm2, which was 0.846 and 0.603 times that of the 316L coating, respectively. Moreover, severe adhesive wear and plastic deformation was transformed into slight adhesive wear and abrasive wear due to the addition of TiC and NbC particles. This study provides new approaches to improving the wear resistance of 316L stainless steel and broadens its application.